The effect of abdominal exercise on diastasis recti abdominal (dra) among postpartum primigravida mother in Kuala Lumpur - Shohaimi, Suhaila (2020)
Abdominal exercise for diastasis recti abdominal (DRA) during postpartum has yet to be explored in research. Despite general exercise programs in current rehabilitation, strength and conditioning programs, few studies have examined the implementation of gradual and progressions abdominal training, and the benefits therein. The objective of this study was to investigate the effects of a progressive abdominal exercise known as Split Tummy Exercise Program (STEP) on the DRA size, pelvic floor muscle (PFM) strength, endurance and perceived urinary distress symptoms and determine the correlation between these variables. STEP module was developed based on literature review and validated by the experts. A randomized control trial study design was carried out at Obstetric and Gynaecology clinic, University Kebangsaan Malaysia Medical Centre (UKMMC) Kuala Lumpur and 41 pregnant women were selected. Later the participants were randomly assigned to the intervention (21 subjects) and control group (20 subjects). The participants were selected among primigravida diagnosed with DRA at 34-week gestations onward if the gap between the abdominal muscle is more than two-finger width measured with finger palpation at the umbilicus. Those with multiple pregnancies, previous abdominal and urogenital surgery, lower caesarian section delivery, and disease that could interfere with PFM strength such as Ehlan Danlos Syndrome were excluded. The intervention group received STEP module consist of three phases of nine abdominal exercises. The progression from phase one to phase two was administered every three weeks and completed phase three at eight weeks postpartum. DRA size ( using 2D ultrasound) and urinary functions (using Urogenital Distress Inventory questionnaire - UDI-6 and Incontinence Impact questionnaire - IIQ-7) were assessed at baseline and 8-weeks postpartum, whereas the PFM strength and endurance (using perineometer) was evaluated at 8-weeks postpartum for both groups. Out of 41 participants, 87.8% were Malays with the mean age of 28 years old (SD=0.56), and most of them (78%) were working. After 8 weeks, both groups had a reduction of DRA size, but result between the group was not significant whereas within-group analysis, DRA size was reduced up to 27% (mean difference: 6.2; 95% CI: 3.7, 8.7) as compared to 8.2% (mean difference:1.66; 95% CI: -1.3, 4.6) in the control group with significant intervention effect at p<0.001. There is a significant difference in PFM strength with a mean difference of 5.89 mmHg (95% CI: 2.10, 9.68; p=0.003) and PFM endurance with the mean difference of 1.11 second (95% CI: 0.01, 2.22; p=0.049) between groups. On the other hand, for urinary function, there is no significant difference in urinary distress symptoms between-group however, within-group analysis, both groups show significant different (p<0.001). In conclusion, the abdominal exercise using eight weeks STEP module effectively reduce the DRA size and could be implemented for mothers with DRA. The strength and endurance of PFM are higher in the STEP group at 8 weeks postpartum and no significant difference in perceived urinary incontinence symptom between the group. Finally, no relationship was found between DRA size and PFM function and perceived urinary distress symptoms. Further research is warranted to ascertain the efficacy of abdominal exercise among a larger population.